Rancang Bangun Sistem Presensi Pegawai Berbasis IP Publik Statik Untuk Meningkatkan Efisiensi dan Akurasi Pencatatan Kehadiran - Ganjar Prasetyo, Karno (Universitas Bengkulu, 2025)
This research aims to create an employee attendance system based on static Public IP from internet service providers. Limitations of conventional attendance systems often include long lines and dependence on specific technologies, such as cards and fingerprint readers. Employees can take attendance flexibly using static public IP technology by utilizing a computer or mobile phone connected to the company's Wi-Fi network. The system development method used is a waterfall, made using the UML visualization model and the PHP programming language with the CodeIgniter framework and MySQL as a database. The test results show that the developed static public IP-based attendance system can increase the efficiency of the attendance process faster and reduce attendance recording errors significantly.